Research towards high-repetition rate laser-driven X-ray sources for imaging applications - Goetzfried, J.; Doepp, A.; Gilljohann, M.; Ding, H.; Schindler, S.; Wenz, J.; Hehn, L.; Pfeiffer, F.; Karsch, Stefan (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
Laser wakefield acceleration of electrons represents a basis for several types of novel X-ray sources based on Thomson scattering or betatron radiation. The latter provides a high photon flux and a small source size, both being prerequisites for high-quality X-ray imaging. Furthermore, proof-of-principle experiments have demonstrated its application for tomographic imaging. So far this required several hours of acquisition time for a complete tomographic data set. Based on improvements to the laser system, detectors and reconstruction algorithms, we were able to reduce this time for a full tomographic scan to 3 min. In this paper, we discuss these results and give a prospect to future imaging systems.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Betatron radiation; Laser wakefield acceleration; Tomography; X-ray imaging